A Pilot Study: N-Staging Assessment of Shear Wave Elastrography in Small Cervical Lymph Nodes for Nasopharyngeal Carcinoma - Guan, Ying; Liu, Shuai; Li, An-Chuan; Pan, Xin-Bin; Liang, Zhong-Guo; Cheng, Wan-Qin; Zhu, Xiao-Dong (Frontiers in Oncology, 2020)
Purpose: To investigate N-staging Assessment of pretreatment Shear wave elastrography(SWE) in small cervical lymph nodes(0.5 cm ≤maximum diameter ＜1cm, intact capsule, no central necrosis, sCLNs) in nasopharyngeal carcinoma (NPC) patients. Methods: Pathological biopsy proven 28 NPC patients with sCLNs shown in pretreatment magnetic resonance (MR) images and 40 target lymph nodes were enrolled. All target lymph nodes were divided into metastasis and benign lymph node groups according to pathology. SWE was used to exam the real time SWE imaging of each target lymph nodes before conducting ultrasonography guided fine needle biopsy. The minimum (Emin), maximum (Emax) and mean (Emean) elasticity indices (kPa) of target lymph nodes were recorded. The SWE examination was repeated three times for the same target lymph node and each elasticity indices for statistic was determined by average of three measurements. SPSS 21.0 statistics software is used for statistical analysis. The receiver operating characteristic (ROC) curve was performed to obtain the cutoff value of elasticity indices of metastatic sCLNs. Statistical significance was assumed when the P＜0.05. Results: Nine lymph nodes were metastatic and 31 were benign. The Emin, Emax and Emean of benign group were 8.15±6.12 kPa, 25.05±12.37 kPa and 16.05±8.29 kPa respectively; Emin, Emax and Emean of metastasis group were 11.5±6.17 kPa, 41.38±17.87 kPa and 23.48±6.50 kPa respectively. The difference of the Emax and Emean between metastasis and benign group were statistically significant（P=0.003 and P=0.018）. The area under the ROC curve of Emin, Emax and Emean of metastasis lymph node were 0.685（P=0.095）,0.785（P=0.010）and 0.765（P=0.017） respectively. Emax of 27kPa and Emean of 17kPa were taken as the cutoff value of diagnosis for metastasis sCLNs: the sensitivity, specificity and accuracy were 77.8% and 100%, 71.0% and 61.3%, 75.0% and 70.0% respectively. Conclusions: Pretreatment SWE has high accuracy in evaluating the sCLNs in NPC patients and is helpful for accurate N staging and survival prognosis. It can be used as a clinical supplementary examination.